2016
DOI: 10.1017/s1751731116000811
|View full text |Cite
|
Sign up to set email alerts
|

Ear tagging in piglets: the cortisol response with and without analgesia in comparison with castration and tail docking

Abstract: The objectives of the present study were to compare the cortisol response caused by ear tagging piglets with the distress caused by other known painful husbandry procedures (e.g. castration and tail docking) and to evaluate the effectiveness of analgesia with meloxicam to reduce the cortisol response caused by these procedures. In total, 210 male piglets were randomised to equal numbers (n = 30) into one of seven groups: a control group which was only handled (H), an ear tagged group that received no analgesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…The doses of meloxicam and ketoprofen were based on the label doses for meloxicam and ketoprofen. These doses have been documented to be effective at reducing post-surgical pain in nursing piglets in similar studies evaluating castration pain [ 2 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The doses of meloxicam and ketoprofen were based on the label doses for meloxicam and ketoprofen. These doses have been documented to be effective at reducing post-surgical pain in nursing piglets in similar studies evaluating castration pain [ 2 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Drugs licensed for use in Canada for the control of pain in swine are currently limited to non-steroidal anti-inflammatory drugs (NSAIDs) such as meloxicam, ketoprofen, and flunixin meglumine. Given as a single injection prior to castration, meloxicam [2,[4][5][6][7] and ketoprofen [8,9] have been shown to provide post-castration pain relief to piglets. The labelled doses of meloxicam and ketoprofen (0.4 mg/kg and 3 mg/kg, respectively) are for older pigs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma cortisol concentrations 4 hours after notching or ear tagging did not differ when compared to sham-processed piglets (Marchant-Forde et al, 2009), but it was probably too late to measure the cortisol response to pain. Indeed, an increase in plasma cortisol was seen 30 and 60 minutes after performing ear notching (Numberger et al, 2016). Yet, no comparison was done at this time between the two techniques.…”
Section: Evidence Of Pain During and Shortly After The Proceduresmentioning
confidence: 99%
“…Pain Numberger et al (2016) evaluated the cortisol level in piglet subject to painful procedures and found that the cortisol response increased as the degree of pain imposed by the process (handling of the pig, marking tail trimming, and castration. Marchant et al (2009) compared tail trimming using two methods cold and hot and found that hot caudectomy presented vocalization with higher frequency and duration than in the cold procedure.…”
Section: Stress Condition Parametermentioning
confidence: 99%